Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Peaceful Eden

Tìm x biết : 

( x - 2 )2 = 1
(2x - 1 )3   = -8
(x + 1/2 )2 = 1/16

adh me
17 tháng 10 2015 lúc 20:05

( x - 2 ) ^2 = 1^2 hoặc  ( x - 2 )^2 = -1^2

=> x - 2 = 1 hoặc x - 2 = -1 

Ta có : x - 2 = 1  => x = 2 + 1 => x = 3 

x - 2 = - 1 => x = - 1 + 2 => x = 1 

( 2x -1 )^3 = -8 

=> (2x-1)^3 = -2^3

=> 2x-1 = -2 => 2x = -2+1 => 2x = -1 => x = -1 :2 => x = -1/2

(x+1/2)^2 = 1/16 

=> (x+1/2)^2 = 1/8^2 hoặc (x+1/2)^2 = -1/8^2

=> x+1/2 = 1/8 hoặc x+1/2 = -1/8 

Ta có : x+1/2 = 1/8 

x= 1/8 - 1/2 

x = 2/16 - 8/16 

x = -6/16 = -3/8

x + 1/2 = -1/8 

x = -1/8 - 1/2 

x = -2/16 -8/16 

x= -10/16 = -5/8 

* ^ là mũ nhé bạn :))

 

 

Peaceful Eden
17 tháng 10 2015 lúc 19:58

Làm lung tung gì thế ông @@